Analisis Perilaku Konsumen dalam Pengambilan Keputusan Pembelian Ikan Segar Dan Produk Olahan Ikan di Kabupaten Garut - Rama Bergawa Raja Dame; Ine Maulina; Asep Agus Handaka Suryana; Atikah Nurhayati (Jurnal Perikanan Unram, 2024)
This research aims to analyze consumer behavior in making decisions to purchase fresh fish and processed fish products at the Garut Fish Culinary Center. Data collection and processing was carried out in January – June 2024 at Tarogong Kaler District, Garut Regency. The research method used is the case study method and the sampling technique is accidental sampling. Data analysis uses Spearman Rank and descriptive marketing mix. In this research, the variables that influence consumers' decision to purchase fresh fish are found, namely product and service motivation, and income motivation for processed fish products. The results of the marketing mix research (7P) are 1) Fresh fish product mix in the form of carp, tilapia, gourami, nilem and catfish, while processed fish products include fried fish and grilled fish. 2) Price mix for fresh fish, carp and tilapia ranging from IDR 35,000-IDR 38,000/kg, gourami IDR 60,000/kg, nilem fish and catfish IDR 25,000/kg and processed fish products starting from IDR 25,000/portion, 3 ) Place mix in the form of first floor for fresh fish commodities and second floor for processed fish product commodities, 4) Promotion mix in the form of word of mouth and business cards, 5) People mix in the form of sellers and buyers, 6) Process mix, including buying and selling flow to payment methods, and 7) Physical evidence mix in the form of banners and menu cards. Key words: Marketing Mix Test, Purchase Motivation, Word of Mouth (WOM) and Spearman Rank Correlation